واقع تبني منظمات الأعمال الصناعية والمسؤولية الإجتماعية دراسة حالة المؤسسة الوطنية للدهن وحدة سوق اهراس - عبير سديرة; وهيبة شلغاف (My University, 2021)
Of the study our current aimed at diagnosing the reality of the Algerian industrial organization demonstrating social responsibility through the field study of the national debt institution and souk ahras unit-and addressing the economic , social and environment, roles of this study in light of a dynamic environment, where uncertainty and risk prevail. We have relied on the interview , observation, recitation, documents and field study tools to test the hypotheses and arrive at the following results: - Social responsibility is an important term and an economic concept of great importance, that combines the achievement of the economic interest of the institution without neglecting the role and environmental states of the institution, so that the National Oil Corporation is interested in training workers on the requirements of industrial security to avoid disasters that affect them first, and the institution and the environment secondly, and is also concerned with the health aspect It provides transportation, and it also provides finance resources for the acquisition of equipment that contributes to protecting the environment, The Foundation also contributes to the economic and social development and the preservation of the environment in light of respecting the organization's laws. ............................................................. هدفت دراستنا الحالية إلى تشخيص واقع تبني المنظمات الصناعية الجزائرية للمسؤولية الاجتماعية من خلال الدراسة الميدانية للمؤسسة الوطنية للدهن وحدة سوق أهراس ، والتطرق إلى الأدوار الاقتصادية، الاجتماعيةة والبيييةة هةال الدراسةة يةة ييةة - - ديناميكية، تسودها حالات عدم التأكد و المخاطرة، ولقد اعتمدنا على المقا لة، الملاحظة والوثائق والمستندات كأدوات الدراسة الميدانية لاختبار الفرضيات والوصول إلى النتائج التالية: إن المسؤولية الإجتماعية إصطلاح هام ومفهوم اقتصادي ذو أهمية فائقة، يجمع ين تحقيق مصلحة المؤسسة الاقتصادية دون إهمةال الةدور الإجتمةاعو والبييةو للمؤسسةة، تيةلم سةتا المؤسسةة الوطنيةة للةدهن تكةوين ال مةال علةى متطلبةات الأمةن الصةناعو لتفادي حدوث كوارث تؤثر عليها أولا، وعلى المؤسسة والمحيط ثانياة وستا أيضا بالجانب الصّحو وتوفير وسائة النقة، كما تقوم توفير المةوارد الماليةة لإقتنةا م ةدات تسةاها ةايةة البييةة، كةال تسةاها المؤسسةة التنميةة الاقتصةادية، الاجتماعيةة والمحافظةة على البيية ية احترام قوانين المنظمة.